The Symbol of Acculturation and Islamic Unity in Nganggung Tradition of Bangka: An Integration of Maqāṣid asy-Syarī’ah with Local Wisdom - Sulaiman, Rusydi; Ibrahim; Muhammad Qomaruddin Ridwan; Ahmad Afnan Anshori; Alfan Shidqon (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2024)
This paper aims to explore the integration of traditional and modern Islam in nganggung tradition of Bangka society. Nganggung is a customary practice of bringing food with specific procedures and attributes to commemorate important Islamic holidays. It existed for a long time as a tradition in Bangka conducted by traditionalists. Recently, modernists also participated in the event, making nganggung a melting pot that blends traditionalists and modernists. While associated with traditional Islam, this practice has also involved modern practices. The research was carried out in Kemuja and Kenanga villages on Bangka Island, using interviews, participatory observation, and a literature review. It addresses three key questions: How is local wisdom in the nganggung tradition expressed in contemporary Bangka society? How can this wisdom strengthen ties between traditional and modern Islam? What is the role of maqāṣid asy-syarī’ah in sustaining this wisdom for lasting harmony? Findings show modernists' participation arises from respect for traditional Islam. While nganggung has adapted to include all groups, changes remain minor. It continues to unite society, sustained by Islamic values and maqāṣid asy-syarī’ah.